(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Ayurveda is the most ancient system of medicine among the different system of medicine existing in the world. In the classification the disease Pandu felt in the group of Varna in which there are significant changes in the normal color of the body. The detail description of Pandu Roga and its classification starts form Ayurvedic Samhitas only. Most of the Acharyas have described five types of PanduRoga, ie. Vatika, Paittika, Kaphaja, Tridoshaja and Mridabhakshhanajanya Pandu. Acharya Charaka, Vagbhatta and Madhava have given Mridakabhakshanjanya type of Pandu. Major etiological factor is Mridabhakashana (soil eating). It may be considered as either oral ingestion of soil or use articles contaminated with soil as unclean hands and fingers or as improperly washed vegetables or eatables. At least one of the Dosha of the individual who has a habit of eating soil gets aggravated. The intake of astringent soil promotes Vata, the salty soil would provoke Pitta, while the intake of sweet soil generates Kapha. Due to the dry nature of the soil, it makes the tissues of the body dry. It will not be digested properly and as a result, it would block various channels of the body. This retards the power of the sensory and motor organs and also the bodily luster, potency and Ojas, thereby producing Pandu Roga which in turn destroys strength, color, and digestion of the patient.